1987
DOI: 10.1152/ajpendo.1987.252.2.e189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term fasting on lipolytic responsiveness in normal and obese human subjects

Abstract: In this study the rate of lipolysis (fatty acid and glycerol release into blood) has been quantified in both normal weight and obese volunteers after both 15 and 87 h of fasting. In each study, the basal rate and subsequent response to epinephrine infusion (0.015 microgram X kg-1 X min-1) were determined. The rate of appearance (Ra) of free fatty acids (FFA) and glycerol were quantified by infusion of [1-13C]palmitate and D-5-glycerol, respectively. Substrate flux rates per unit of body fat mass and lean body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 5 publications
12
100
3
Order By: Relevance
“…Interestingly, the decrease in cold-stimulated glucose uptake after fasting is specific for BAT, since this was not observed in other tissues. In subcutaneous WAT, [ 18 F]FDG uptake was increased, which may be explained by an increased triacylglycerol/fatty acid cycling, whereby α-glycerol phosphate, which provides the backbone for esterification of NEFAs, is derived from plasma glucose uptake, as demonstrated previously [35]. The energy required for this process might actually contribute to the increase in energy expenditure that we measured upon fasting [36].…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, the decrease in cold-stimulated glucose uptake after fasting is specific for BAT, since this was not observed in other tissues. In subcutaneous WAT, [ 18 F]FDG uptake was increased, which may be explained by an increased triacylglycerol/fatty acid cycling, whereby α-glycerol phosphate, which provides the backbone for esterification of NEFAs, is derived from plasma glucose uptake, as demonstrated previously [35]. The energy required for this process might actually contribute to the increase in energy expenditure that we measured upon fasting [36].…”
Section: Discussionsupporting
confidence: 66%
“…This is in accordance with our previous findings of the readily accessible pool size of VLDL-TAG [22]. VLDL-TAG concentrations and SA were spline fitted to minimise analytical variation that may occur when raw data are used in non-steady-state equations (Sigmaplot 11.0, Systat Software, Chicago, IL, USA) [23]. VLDL-TAG secretion and clearance were calculated according to the following equations [17,18]:…”
Section: Methodssupporting
confidence: 67%
“…38 For instance, differences in catecholamines, insulin and adenosine concentrations, and adipose tissue blood¯ow between lean and obese have been reported. 32 ± 34,39 ± 41 Wolfe et al 42 and Webber et al 43 also reported a decreased rate of appearance of FFA per kg fat mass during fasting in obese compared to lean males. However, when expressed per kg of lean body mass, FFA turnover is higher in obese or upper-body obese than in lean or lower body obese subjects 43,44 (Figure 1).…”
Section: Introductionmentioning
confidence: 94%
“…Although resting arterial FFA concentration is usually higher in obese than lean subjects, the increase upon stimulation is often reduced, resulting in similar or even lower FFA concentrations in the obese. 34,42,43 Total and forearm skeletal muscle blood¯ow has been shown to be similar in lean and obese subjects at rest, but adrenaline-or isoprenaline-induced increases in blood¯ow were blunted in the obese. 34,43 Weight loss did not normalise the blunted FFA and blood¯ow response.…”
Section: Fatty Acid Delivery and Transportmentioning
confidence: 99%
See 1 more Smart Citation